Análise da reativação do vírus herpes simples tipo 1 após procedimentos odontológicos pela técnica da reação em cadeia da polimerase - Luciano Marques da Silva (2006)
The herpes simplex virus type 1 (HSV-1), a DNA virus, is a member of the human herpesvírus family (HHV). The majority of the population (90%) have antibodies to HSV-1, and as many as 40% of these individuals may develop secondary herpes. Shedding of HSV-1 in the oral mucosa can be induced by many factors such as stress, sunlight, menstruation and physical trauma. The aim of the present study was to evaluate the impact of dentistry surgery procedure on HSV-1 shedding in the oral mucosa. Thereby, 48 patients submitted to extraction of the third molar and 48 patients submitted to restorative procedures were included in this study. Venous blood collection was performed in order to verify IgG sorology for HSV-1. Oral swabs were performed before and a week later the procedures in order to investigate HSV-1 by Nested-PCR. The results did not show any statistical differences between the frequency of positive individuals to HSV-1 after surgery (4.2%), compared to the control group (2.1%). There results indicate that shedding of HSV-1 in the oral mucosa is not increased by surgical trauma.